Experimental Analysis of Heat and Mass Transfer in a Packed Bed - Suryanarayana, K. V.; Rao, G. Srinivasa; Prasad, D. M. R.; Sharma, K. V.; Sarma, P. K. (Faculty Mechanical Engineering, UMP, 2011)
Experiments have been conducted to study the effect of mass flow rate on heat and mass transfer coefficients in a packed bed. It has been observed that an increase in mass flow rate of water increases the heat and mass transfer coefficients by 1.7–1.9 and 3.2–3.8 times, respectively, at 55–95 °C. The diffusion of oxygen from packed bed inlet water, obtained from experimental data, can be used to estimate the mass transfer coefficients. The theoretical equation available in literature is compared and satisfactory agreement has been observed. The increase in inlet water temperature decreases both the heat and mass transfer coefficients by 60% and 25%, respectively, because of the reduced driving force. The increase in oxygen concentration in inlet water has no significant effect on either heat or mass transfer coefficients.